Between federation and confederation (Economic and Political Thought, 2018)
The aim of this article is to analyse the political system in integratingEurope, first of all to make an attempt to compare its confederal and federalcharacteristics. The author tries to answer a number of research questions.Does the European Union, as a union of states, remain primarily a confederation,or is it going towards a federation over time? And if so, in whichareas does it resemble a federation most? Did the eurozone crisis becomea catalyst for change, or was it easier to achieve an “institutional breakthrough”towards a federation? Or is Europe still waiting for a convenient“constitutional moment” for these changes?
Keywords: federation, confederation, institutional breakthrough, European Union